Research on crack propagation law of rotating bending fatigue cropping process based on cusp catastrophe theory. (April 2022) - Xu, Jiayi; Zhou, Qiang; Tao, Jishao; Sun, Xudong; Zhao, Qing; Fu, Shulin; Yang, Ning; Guo, Weijian; Zhang, Lijun
Graphical abstract: Highlights: Crack stable-jump propagation alternately is studied by catastrophic theory. It is found that changing the loading parameters can control crack form in cropping. Loading curve based on catastrophic theory is built to improve cropping quality. Abstract: A large number of experimental results show that in variable load low-stress fatigue cropping there are two forms of fatigue crack propagation, stable crack propagation and sudden-jump crack propagation, but sudden-jump crack propagation seriously affects cropping section quality. In this paper, the process of crack propagation under cropping is analyzed, and the condition of alternate stable-jump crack propagation under circumferential rotating bending fatigue loading is proposed from the fracture mechanism. Based on the energy method, the cusp-catastrophe model potential function of cropping process is constructed, and with XFEM (extended finite element) and total potential energy catastrophe theory, the multiple catastrophe positions in the cropping process are obtained. The results of the AE (acoustic emission) measurement experiment in cropping confirm the phenomenon of multiple catastrophe in the process of fatigue crack propagation. The loading curve based on catastrophe theory is obtained by fatigue strength theory. Compared with current common loading curves, the obvious sudden-jump crack propagation phenomenon is eliminated basically, no obvious catastrophe trace is observed in the propagation area, and the fracture area is reduced by 54.65%, which significantly improves the quality of cropping section.